The motivation in the performance of the inspection functions: inspection service at the university - Falcón Armas, Andrés (Avances en Supervisión Educativa, 2014)
A summary of Hackman and Oldham job characteristics model (1976, 1980) is presented as follows. The five cores job dimensions and their relationships with the critical psychological states and with the personal and organisational outcomes are also defined. Likewise, observed is the modulatory role of self-efficiency variables, intensity of the personal development and self-satisfaction needs with the context. The predictive theoretical relationship model is related to the post of inspector of education in the field of educational organisations, including universities.